PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PBL PADA MURID KELAS III SDN PANDEAN LAMPER 03 - Puput Malia Rosalina; Ferina Agustini; Titik Haryati; Estiyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The results of learning mathematics at SDN Pandean Lamper 03 are still low. This is due to students' low problem-solving abilities and still conventional learning, which results in students being less active. The purpose of this research is to use the Problem Based Learning (PBL) model to improve the mathematics learning outcomes of class III students at SDN Pandean Lamper 03 Semester I Year 2022/2023. PTK consists of two cycles, each cycle consisting of four stages, planning, implementing, observing and reflecting. This study involved 27 grade III students as participants. Data collection tools in the form of tests and documentation. Based on research findings, the PBL model can improve mathematics learning outcomes. Student learning outcomes experienced a better increase than before the action, only 48% of students completed. However, after the action, there was an increase in learning outcomes in the first cycle of 70% and increased to 85% in the second cycle.